Religión contra democracia: el neoconservadurismo evangélico en el Perú del siglo XXI = Religion Against Democracy : Evangelical Neoconservatism in 21st Century Peru - Rivera, Dario Paulo Barrera (Ciencias sociales y religión, 2021)
Participation of evangelicals in politics is a phenomenon that has become common in Latin America in the post-dictatorship period. This article analyzes the more recent phenomenon of the support of evangelicals for candidacies and political projects of the extreme right that make up a “religious neo-conservatism.” We focus our attention on the political practice of evangelicals in Peru, in the contemporary period to the government of Donald Trump that welcomed the transnational religious policy “Capitol Ministries.” We analyze the understanding of political power in the evangelical tradition and its theological arguments for its militancy on the extreme right. We rely on a remote ethnographic survey of electoral campaign material from the Popular Renovation party and its pastoral candidates for the 2021 elections in Peru. We work with the hypothesis that evangelicals’ understanding of political power reduces democratic space by transforming adversaries into enemies that must be “exterminated,” similar to the Bolsonaro phenomenon in Brazil.